Problem Supervisi Dan Evaluasi Pendidikan (Kajian Tentang Problematika Guru di Sekolah Dalam Perspektif Supervisi Pendidikan ) - Henny Nikolin Tambingon; Youlanda A.M Rawis; Meisie Lenny Mangantes; Yulmi H. Mottoh (Peneliti.net, 2022)
The purpose of this research is to obtain empirical data regarding the problems faced by teachers in schools. The type of research used in this research is library research or library research, namely research conducted through collecting data or scientific writings that aim at research objects or data collection that is library in nature, or studies that are carried out to solve a problem that basically rests on on a critical and in-depth review of relevant library materials. The results of the study show that the teacher is a figure who is a role model in all matters, both explicit and implied behavior, so that Counseling Guidance really functions as a guide for students to lead them to be the best. In addition to directing the goals of good students, Counseling is also very helpful for educators who are not diligent enough to be diligent, who experience difficulties in being disciplined, who experience boredom due to work routines will find a way full of benefits and enthusiasm, educators who are less democratic will become democratic which in the end with Counseling Guidance makes it directed in all matters to determine the solution.